Combination of nanolamellae and PDA coating on promoting the long-term adhesion, proliferation, and differentiation of osteoblasts. (20th May 2020) - Zhao, Baisong; Zheng, Zi-Li; Liu, Wei; Yin, Hua-Mo; Lan, Ri-Tong; Xu, Ling; Xu, Jia-Zhuang; Song, Xingrong; Li, Zhong-Ming
Abstract: Nanotopographical and chemical cues were collectively introduced onto the poly(L-lactic acid) (PLLA) surface via alkali etching and polydopamine (PDA) coating. The surface pattern was made of dense-packed PLLA lamellae, and the PDA coating did not change the feature of surface topography. Both nanotopographical pattern and PDA coating showed long-term stability in cell culture medium for two weeks. In vitro evaluations displayed that there was a synergy between nanotopography and PDA coating on cell adhesion, proliferation, and differentiation of osteoblasts, even for a culture period of two weeks. This sustained effect was attributed to the activation of the wnt/β-catenin pathway. These results hold a promising prospect for the application of bone repair grafts. Graphical abstract: Nanotopographical and chemical cues were collectively introduced onto the poly(L-lactic acid) (PLLA) surface. In vitro evaluations proved that nanotopography and PDA coating synergy promoted cell adhesion, proliferation, and differentiation of osteoblasts. Image 1 Highlights: Nanotopographical and chemical cues were collectively introduced onto the poly(L-lactic acid) surface. The nanotopographical pattern and PDA coating showed long-term stability. The cell adhesion, proliferation, and differentiation of osteoblasts are significantly promoted.